Epidemiological aspects of type 2 diabetes in the young - Lyudmila Alexandrovna Suplotova; Larisa Nikolaevna Bel'chikova; Nadezhda Alexandrovna Rozhnova (Сахарный диабет)
Aim. To study prevalence and incidence of type 2 diabetes in the young population of Tyumen region. Materials and methods. The study included 201 adult patient with type 2 diabetes mellitus (DM). The first group included 99 patients with disease onset before 35 years, while the second group included 102 patients with disease onset after 40 years. We have used a Tyumen regional diabetes register data, covering last 10 years period. We assessed the prevalence and incidence of type 2 DM and its vascular complications. Results. The prevalence of type 2 DM in patients with disease manifest before 35 years increased by 2,7 times and the incidence ? by 2,1 times during last 10 years. We noted predominance of retinopathy and nephroopthy in the structure of vascular complications in this group. Conclusion. Patients with type 2 DM onset before 35 years are characterized by increasing prevalence and incidence during last 10 years, as well as rapid development of late diabetic complications with a predominance of microangiopathy.